(untitled) (Orlando, 1987)
Contents: Executive Advisory Board; Editorial Advisory Board; Foreword; Preface; Guide to Using the Encyclopedia...
Keywords: Physical sciences,Khoa học vật lý; Engineering,Technology,Encyclopedias,Kỹ thuật,Công nghệ,Bách khoa toàn thư